2010
DOI: 10.4161/viru.1.3.10896
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ante-mortem assays to assess progression/regression of paratuberculosis in individual dairy animals

Abstract: Johne's disease, caused by Mycobacterium avium, subspecies paratuberculosis (MAP) is becoming increasingly widespread on dairy farms worldwide, due in part, to the absence of vaccine/drug or curative modalities.  This spread is of concern since MAP is at the center of a controversy as to its role in Crohn's disease.  None of the methods presently available to define paratuberculosis in cattle have been examined for their ability to assess progression/regression of any treatment or intervention of this disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 43 publications
4
21
0
Order By: Relevance
“…Evidence supporting positivity of the three ELISA-only-positive dams (dams of calves 1-2, 3-3 and 4-1) is that 2 (calves 1-2 and 4-1) of these 3 calves tested both ELISA-and fecal-positive-both calves were born prior to initiating a Dietzia treatment that cured the dams-prevented development of fecal shedding. [13][14][15] Therefore, based on the predictive accuracy of the Allied Monitor ELISA found with the previous 75 adults, 37 plus similar accuracy found for the dams in the present study, the probability that all animals (dams and calves) that were only ELISA testpositive as adults, irrespective of their age, are not paratuberculosis-positive is extremely remote.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Evidence supporting positivity of the three ELISA-only-positive dams (dams of calves 1-2, 3-3 and 4-1) is that 2 (calves 1-2 and 4-1) of these 3 calves tested both ELISA-and fecal-positive-both calves were born prior to initiating a Dietzia treatment that cured the dams-prevented development of fecal shedding. [13][14][15] Therefore, based on the predictive accuracy of the Allied Monitor ELISA found with the previous 75 adults, 37 plus similar accuracy found for the dams in the present study, the probability that all animals (dams and calves) that were only ELISA testpositive as adults, irrespective of their age, are not paratuberculosis-positive is extremely remote.…”
Section: Discussionmentioning
confidence: 77%
“…Stage III animals had signs of early clinical disease (change in fecal consistency, loss of appetite and reduced milk production, all noted by the author) and were either ELISA-and/ or fecal-positive, whereas, Stage IV animals had severe, end-stage clinical disease, irrespective of whether they were ELISA-and/ or fecal-negative/positive (almost all were fecal shedding). The magnitude of ELISA values and fecal shedding cfu were not used to define these stages, since previous longitudinal assessment 37 showed that there was no correlation. All dams were tested three to four times per year over their lifetime and maintained in the herd until local veterinarians humanely euthanized recumbent, emaciated and/or cachectic animals that could not rise and stand on their own by intravenous injection of a sodium pentobarbital solution (Fatal Plus, 6 g/ml) at a dose of 1 ml per 4.5 kg body weight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By testing a combination of Allied's MAP ELISA, bacterial fecal growth and serum agar gel immunodiffusion (AGID), Click has determined that ELISA analysis is the most accurate and reliable testing method for changes in the disease status of an individual by best-fit longitudinal increases/decreases in serum ELISA values with a sensitivity of 100%. 26 Click was able to determine that Allied's ELISA detected MAP antigens at a much earlier time point in the progression of disease, as compared with other leading ELISA methods, leading to its very high sensitivity. These ELISA values did not directly correlate with the fecal shedding of MAP, which as it turns out, is advantageous since serum ELISA values were detectable before fecal shedding was detected.…”
mentioning
confidence: 99%
“…17,18,23 Reports of variability in the sensitivity of the ELISA for the diagnosis of MAP-positive sera for isolates derived from different host species is not surprising since antigen preparation is not standardized. [24][25][26] Although the current challenges discussed here have been plaguing Johne disease researchers for some time, recent events in research conducted by Click et al [26][27][28][29] shed a sense of optimism on a somewhat overwhelming subject. 29 This data shows a direct impact of Dietzia not only on the shedding of MAP bacteria in the feces but also on the disease status of the individual.…”
mentioning
confidence: 99%